Análise dos efeitos da emenda constitucional n° 29/ 2000 nas decisões alocativas dos estados e Distrito Federal - Grell, Armando Pereira (2015)
Constitutional Amendment No. 29 of 2000 (EC No. 29/2000) was approved with the purpose of ensuring adequate financial resources for public health and of involving and committing the three government levels by the funding from the public health sector in the country. The objective of this study is to analyze the allocative decisions of the states and Federal District influenced by EC N ° 29/2000. To carry out this study has been conducted an inferential, explanatory quantitative and qualitative research, addressed using the empirical method to analyze historical data for expenditures allocations to the public health of the States and Federal District in relation to the EC No. 29/2000. The data were analyzed using mathematical methods and statistical techniques used in econometrics. The study has identified that the differences in the fiscal and socioeconomic environments of the states produce different decisions in the public health sector. During the period analyzed, the EC No. 29 and the net income per capita have influenced the variability of the indicator that measures the application rate in the public health sector. However, more financial resources in the sector did not ensure the public health improvement service. Partly managers do not have the appropriate skills to promote the change process with the purpose to improve the effectiveness and efficiency of the sector. This situation is aggravated by the party-political factors that interfere in the sector by means of promoting people without proper qualification and by means of making decisions based on political criteria to the detriment of technical and operational criteria.